Acquired Personality Disturbances After Meningioma Resection Are Strongly Associated With Impaired Quality of Life. Issue 2 (23rd October 2019) - Barrash, Joseph; Abel, Taylor J; Okerstrom-Jezewski, Katrina L; Zanaty, Mario; Bruss, Joel E; Manzel, Kenneth; Howard, Matthew; Tranel, Daniel
Abstract: BACKGROUND: Some patients experience long-term declines in quality of life following meningioma resection, but associated factors are not well understood. OBJECTIVE: To investigate whether long-term declines in quality of life (specifically impaired adaptive functioning) after meningioma resection are associated with specific personality disturbances that often develop with lesions in ventromedial prefrontal cortex (vmPFC). METHODS:  We studied 38 patients who underwent resection of meningioma, 18 of whom had vmPFC lesions and 20 with lesions elsewhere (non-vmPFC). A total of 30 personality characteristics were rated by spouse or family, and a neuropsychologist blindly rated adaptive functioning an average of 3.8 yr postresection. Relevant personality disturbance was defined by a priori process: the presence of "conjoint personality disturbance" required specific disturbances in at least 2 of 4 types of disturbance: executive disorders, disturbed social behavior, emotional dysregulation, and hypoemotionality. RESULTS: Fourteen patients had impaired adaptive functioning: 12 had vmPFC lesions and 2 had non-vmPFC lesions. Fourteen patients had conjoint personality disturbance, and 12 of them had impaired adaptive functioning. By contrast, among the 24 patients who did not have conjoint personality disturbance, only 2 had impaired adaptive functioning. Mediation analysis showed that the association between vmPFC lesions and impaired adaptive functioning was mediated by the negative impact of acquired personality disturbance on adaptive functioning. CONCLUSION: Anterior skull base meningiomas plus resection surgery may result in specific personality disturbances that are highly associated with impaired adaptive functioning at long-term follow-up. These patients may benefit from early counseling regarding potential personality changes and their implications for adaptive functioning.